Religious education in public schools: a study based on the BNCC (Research, Society and Development, 2020)
Objective: This article aims to analyze the theoretical and methodological contributions that BNCC presents as significant changes for Religious Education. Methodology: This is a bibliographic review entitled, State of the Art, which made it possible to map the scientific articles published in the last 05 years, contributing to the composition of the theoretical framework on Religious Education implemented from BNCC. The following problem was raised: what do the scientific publications of 2015-2020 point out about aspects of Religious Education at BNCC considering their theoretical and methodological contributions? Results: The mapping points out among the results that research and dialogue are ways of realizing what is established as specific competences for Religious Education, in Elementary Education, in convergence with the BNCC. In the time frame, only four articles are directly related to the object of investigation. Conclusion: The Sciences of Religions constitute an important channel to enable the reflective exercise on Religious Education at school.